A Benefit of Being Heavier Is Being Strong: a Cross-Sectional Study in Young Adults - Gill A. ten Hoor; Guy Plasqui; Annemie M. W. J. Schols; Gerjo Kok (SpringerOpen, 2018)
Abstract Background In this study, the main hypothesis is that heavier people enjoy strength exercises more than normal-weight people, mediated by fat-free mass and muscle strength. Further, it is hypothesized that heavier people are better in strength exercises and enjoy strength exercises more compared to aerobic exercises. Methods In a cross-sectional study, height, weight, body composition (i.e., fat mass and fat-free mass by underwater weighing), muscle strength (i.e., one-repetition maximal strength for the leg press and chest press), maximal aerobic exertion (VO2max) during cycle ergometry, and psychological determinants (i.e., attitudes, intentions, and self-determined motivations for strength exercises and aerobic exercises using questionnaires) were measured in 68 participants (18-30 years). Results Significant correlations between weight/BMI and fat-free mass (index) (r values = .70-.80, p values < .001), fat-free mass and muscle strength (r values = .35-.55, p values < .05), and muscle strength and attitudes, intentions, and motivation for strength exercises were found (r values = .29-.43, p values < .05); BMI was related to psychological determinants via fat-free mass and muscle strength. Furthermore, participants with a higher BMI are significantly better in strength exercises, more intrinsically motivated, and less motivated to do strength exercises compared to aerobic exercises (all p values < .05). Trends in the same direction were found for the following variables: instrumental attitude, experiential attitude, and intention (p values < .1). Conclusions Strength exercises could be more appropriate for heavier people and might therefore be a valuable component in physical activity programs for people who are overweight or obese.